2000
DOI: 10.1093/ndt/15.8.1175
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of taurine against gentamicin‐induced acute tubular necrosis in rats

Abstract: Our observations suggest that taurine treatment attenuates the accumulation of gentamicin within kidney tissue and counteracts the deleterious effect of gentamicin on renal tubular function. They may have potentially important clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
114
5
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(143 citation statements)
references
References 19 publications
20
114
5
1
Order By: Relevance
“…Researchers also observed that creatinine (Cr) level is a more accurate measurement for glomerular impairment than urea levels/Cr clearance. [42,43] Our study results coincide with earlier reports that a significant increase in plasma urea and creatinine or decrease in potassium levels [40,41,44] might indicate a nephrotoxic condition in GEN-treated rats and may be due to kidney damage caused by the enhanced generation of ROS. These findings correlated well with the renal histological examination, which revealed renal tubular necrosis and interstitial nephritis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Researchers also observed that creatinine (Cr) level is a more accurate measurement for glomerular impairment than urea levels/Cr clearance. [42,43] Our study results coincide with earlier reports that a significant increase in plasma urea and creatinine or decrease in potassium levels [40,41,44] might indicate a nephrotoxic condition in GEN-treated rats and may be due to kidney damage caused by the enhanced generation of ROS. These findings correlated well with the renal histological examination, which revealed renal tubular necrosis and interstitial nephritis.…”
Section: Discussionsupporting
confidence: 91%
“…[1] The present study confirmed that GEN at a dose of 100 mg/kg b.w for eight days produces nephrotoxicity, [40,41] as evidenced by the impairment in glomerular function. Researchers also observed that creatinine (Cr) level is a more accurate measurement for glomerular impairment than urea levels/Cr clearance.…”
Section: Discussionsupporting
confidence: 84%
“…Support for the concept of distinctly different responses to aminoglycosides in vivo and in vitro also exists for their nephrotoxic side effects. Tubular necrosis is a confirmed route of cell death in vivo 24 while renal cell lines show apoptosis in response to aminoglycosides. 25 Multiple organelles are involved in the ototoxic cascade following chronic administration of aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%
“…The blood analyses were done by Meril's auto-analyser. [17][18][19] (Merilyzer Auto-Quant 100); this is a fully automatic biochemical analyser.…”
Section: Methodsmentioning
confidence: 99%